Video surveillance of nesting birds - Ribic, Christine A.; Thompson, Frank R. (Frank Richard); Pietz, Pamela J. (Studies in avian biology, 2012)
Declining bird populations, especially those that breed in North American grasslands, have stimulated extensive research on factors that affect nest failure and reduced reproductive success. Until now, this research has been hampered by the difficulties inherent in observing nest activities. Video Surveillance of Nesting Birds highlights the use of miniature video cameras and recording equipment yielding new important and some unanticipated insights into breeding bird biology, including previously undocumented observations of hatching, incubation, fledging, diurnal and nocturnal activity patte.